UPAYA PENINGKATAN HASIL BELAJAR PEMBAGIAN MELALUI GAME EDUKASI PIRING PINTAR KELAS 4 SD KADIREJO 02 - Yohanna Dwi Apriliani; Herry Sanoto (ACADEMIA: Jurnal Inovasi Riset Akademik, 2026)
ABSTRACT Difficulties in learning division with remainders at the elementary school level are often reflected in limited classroom participation, low learning motivation, and unsatisfactory academic achievement. To address these challenges, an educational game supported by the Piring Pintar media and the porogapit method was introduced in a fourth-grade classroom at SD Kadirejo 02. This approach was designed to provide participants with a more concrete, engaging, and accessible understanding of division with remainders. The study was conducted as Classroom Action Research implemented across two cycles, each consisting of planning, action, observation, and reflection stages. Data were collected through classroom observations, learning achievement tests, interviews, and documentation to capture changes occurring throughout the learning process. The findings revealed notable improvements in several aspects of learning. Participant engagement increased from 70% to 88%, while learning motivation rose from 72% to 89%. Learning outcomes also showed substantial progress, with mastery achievement improving from 68% to 90%. These results indicate that combining educational games with the Piring Pintar media and the porogapit method contributed positively to participants’ understanding of division with remainders while creating a learning environment that encouraged active involvement and sustained motivation. The implementation of this approach therefore demonstrated its potential to enhance the overall quality of mathematics learning for fourth-grade participants at SD Kadirejo 02. ABSTRAK Pembelajaran pembagian bersisa pada peserta didik sekolah dasar sering menghadapi kendala berupa rendahnya partisipasi belajar, kurangnya dorongan untuk terlibat aktif, serta capaian hasil belajar yang belum optimal. Kondisi tersebut mendorong penerapan game edukasi yang dipadukan dengan media Piring Pintar dan metode porogapit sebagai upaya menghadirkan pengalaman belajar yang lebih konkret, menarik, dan mudah dipahami oleh peserta didik kelas IV SD Kadirejo 02. Implementasi tindakan dilakukan melalui Penelitian Tindakan Kelas yang berlangsung dalam dua siklus. Setiap siklus dikembangkan melalui rangkaian perencanaan, pelaksanaan tindakan, observasi, dan refleksi. Data penelitian diperoleh melalui observasi, tes hasil belajar, wawancara, serta dokumentasi untuk menggambarkan perubahan yang terjadi selama proses pembelajaran. Perubahan positif tampak pada berbagai aspek yang diamati. Tingkat keaktifan peserta didik meningkat dari 70% menjadi 88%, sedangkan motivasi belajar mengalami kenaikan dari 72% menjadi 89%. Perkembangan serupa juga terlihat pada hasil belajar, yang ditunjukkan oleh peningkatan ketuntasan dari 68% menjadi 90%. Temuan ini menunjukkan bahwa integrasi permainan edukatif dengan media Piring Pintar dan metode porogapit tidak hanya membantu peserta didik memahami konsep pembagian bersisa secara lebih bermakna, tetapi juga menciptakan suasana belajar yang mendorong keterlibatan dan motivasi belajar. Dengan demikian, pendekatan tersebut berkontribusi nyata terhadap peningkatan kualitas pembelajaran matematika di kelas IV SD Kadirejo 02.